Rencana Penerapan Sistem Khilafah di Indonesia - arum ayu lestari, arum ayu; Fadila, Anisa Rizki (LPPM UNU BLITAR, 2023)
The state is an area that becomes an umbrella for the people under its auspices. Of course, in a country, a system is needed to organize society so that it is in one command line. So that the country can maintain order and order. The Indonesian state with a majority population as Muslims is an easy target for groups who want to establish a caliphate state, even though Indonesia has implemented a democratic system, because it sees the background of the Indonesian people consisting of various religions. This research method uses literature studies, namely literature studies which contain related theories that have relevant relationships with the problems studied by researchers. So from this research produces that the khilafah system cannot be applied in Indonesia. Because even though what is applied is not a caliphate system, the religious rights of the community are still respected and upheld, even being the basis in law, for example, related to marriage law and inheritance rights.